Ventricular Septal Defect with Pulmonary Valve Endocarditis with Vegetation - Successful Surgical Treatment in Apollo Hospitals Dhaka - Zahangir, NM; Hasan, MK; Meher, T; Basak, RK; Rayhan, MN; Ahmed, N; Haider, MZ (Pulse, 2017)
Background: Pulmonary valve vegetation with ventricular septal defect needs early surgical intervention. Case presentation: A 21 years old man got admitted in Apollo Hospitals Dhaka, with the complaints of dyspnoea on exertion since childhood. Echocardiogram revealed a large perimembranous ventricular septal defect, moderate pulmonary stenosis, vegetation attached with pulmonary valve leaflet moving during systole & diastole. During operation ventricular septal defect was closed by dacron patch. Large vegetation was excised from anterior cusp of pulmonary valve. A perforation in right cusp of pulmonary valve was repaired with pericardial patch. Transesophageal Echocardiogram revealed well functioning ventricles and no leakage through the repaired Ventricular Septal Defect and pericardial patch in pulmonary valve leaflet. Result: Culture Sensitivity from vegetation showed no growth and histopathological examination revealed tissue consistent with vegetation of Pulmonary Valve. Post- operative echocardiogram showed no residual shunt or vegetation. The patient was discharged on 8th post operative day in good general condition and is doing well till now. Conclusion: Pulmonary valve endocarditis with vegetation with ventricular septal defect is a rare association. Early surgical intervention gives good outcome. Pulse Vol.9 January-December 2016 p.69-72